#### Answer

$6x+6$

#### Work Step by Step

$(2x+6)*3x +12 = (x+2)*y$
$6x^2+18x+12 = (x+2)*y$
$(x+2)(6x+6) = (x+2) *y$
$6x+6 =y $

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$6x+6$

$(2x+6)*3x +12 = (x+2)*y$
$6x^2+18x+12 = (x+2)*y$
$(x+2)(6x+6) = (x+2) *y$
$6x+6 =y $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.